Carbapenemase-producing Klebsiella pneumoniae strains in Switzerland: human and non-human settings may share high-risk clones. (March 2022) - Campos-Madueno, Edgar I.; Moser, Aline I.; Jost, Géraldine; Maffioli, Carola; Bodmer, Thomas; Perreten, Vincent; Endimiani, Andrea
HIGHLIGHTS: Swiss national data about carbapenemase-producing K. pneumoniae (CP- Kp ) are scarce, especially for the human setting. We analysed 285 Kp genomes (170 CP- Kp ) isolated in Switzerland from humans and non-humans. We identified five top STs for CP- Kp : ST512, ST258, ST101, ST11 and ST307. ST512, ST258 and ST101 strain were of human origin only. ST11 and ST307 strains were from both human and non-human settings. ABSTRACT: Background: The spread of carbapenemase-producing Klebsiella pneumoniae (CP- Kp ) strains belonging to high-risk sequence types (STs) is a concern. For Switzerland, national data about the molecular features (especially the STs) of CP- Kp of human origin is not available. In veterinary clinics, ST11 and ST307 bla OXA-48 -possessing K. pneumoniae strains have been recently reported. Methods: We analysed a collection of 285 K. pneumoniae genomes (170 were CP- Kp ) isolated in Switzerland from human and non-human sources during 2006–2020. Whole-genome sequencing, core genome phylogenies and public databases were used to present a detailed overview regarding carbapenemases, STs and plasmids. Results: The top five STs were (main carbapenemase gene) ST512 ( bla KPC-3 ), ST258 ( bla KPC-2 ) and ST101 ( bla OXA-48 ), consisting of strains of human origin only, and ST11 ( bla OXA-48 ) and ST307 ( bla OXA-48 ) strains isolated from human, animal and environmental sources. However, during 2016–2020, the main STs for CP- Kp were ST11 (17.6%), ST307 and ST101 (both 14.7%), whereas ST258 (5.9%) and ST512 (4.4%) significantly declined. Most carbapenemase genes were carried on plasmids already described. Core genome analysis revealed that ST11 K. pneumoniae of animal and human origin were closely related, whereas those of ST307 were distant. Conclusions: We described, for the first time, the features of the CP- Kp circulating in Switzerland in human and non-human settings. Our genomic analysis revealed that the emerging high-risk ST11 and ST307 lineages were often isolated from non-human settings. This study provided a baseline for further whole-genome sequencing-based One-Health surveillance of CP- Kp and emphasized the need for metadata to track dissemination routes between the different settings.